Assessment of causal relationship amid enablers of successful transition of management succession in family-owned businesses – a study of the South Asian Nations - Agrawal, Reena; Saxena, Charu; Mendon, Suhan; Popescu, Virgil; Birau, Ramona; Caruntu, Genu Alexandru (Journal of Business Economics and Management, 2025)
The present study was done to evaluate the causal relationship amid the enablers of successful transition of management succession in family-owned business in South Asian Nations. This was an empirical study where owners of family-run business across various South Asian countries were interviewed. In this study we used the Decision-Making Trial and Evaluation Laboratory (DEMATEL) approach to examine the causal relationship among the twelve variables which were identified by examining the existing literature. The findings of the research demonstrated that formal education, well defined succession plan, early affiliation in business etc. formed the cause group and shared vision for future, active involvement of the successor/s in the succession process, tacit knowledge transfer, building trust and credibility in successors and competence over gender etc. formed the effect group.